Functional characterization of LDL receptor gene variants found in patients with clinical diagnosis of familial hypercholesterolaemia - Alves, A.C. (2020)
Aim: Familial Hypercholesterolaemia (FH) is an autosomal disorder of lipid metabolism presenting increased cardiovascular risk due to lifelong exposure to high LDL levels. LDLR mutations are the cause of disease in about 90% of the cases, but proof of pathogenicity has only been obtained for about 10% of the variants. The lack of functional characterization of variants found in patients with a clinical diagnosis of FH makes it difficult to reach a definite FH diagnosis. In the Portuguese Familial Hypercholesterolemia Study (PFHS), 142LDLR alterations were found in 861 index patients and their relatives up to date. Until now, 82 of these alterations have already been proved to be mutations causing disease or are established null alleles and 15 were classified by in vitro studies as non-pathogenic. The remaining 38 variants, 21 of unknown significance (VUS), found in 102 index cases have not been yet functionally characterized.